Low Birth Weight of Newborns and Its Association with Demographic and Socio-economic Determinants: Findings from Multiple Indicator Cluster Survey (MICS) Bangladesh 2019 - Siddiqi 1*, Md. Nure Alam; Muyeed 2, Abdul; Haque 3, Md. Nuruzzaman; Abdul Goni 3, Md.; Shadhana 4, Supti Chakrabarty (Shahroud Journal of Medical Sciences, 2021)
Background: Low Birth Weight (LBW) is considered as one of the major public health problems which is an important determinant of morbidity and mortality among newborn babies in Bangladesh. This study aimed to examine the current prevalence of LBW and its association with different socio-economic and demographic determinants in the context of Bangladesh. Methods: The cross-sectional data for this study were extracted from the Multiple Indicator Cluster Survey (MICS) Bangladesh 2019, which was carried out in 2019 by the Bangladesh Bureau of Statistics (BBS) in collaboration with UNICEF Bangladesh, as part of the Global MICS Program. To examine the association of LBW with other selected determinants, Chi-square (χ2) test was performed and a logistic regression model was used to explore the net effect of determinants on LBW using odds ratio (OR). Results: Using the sub-sample of nationally representative data, the study reveals that the prevalence of LBW in Bangladesh was 13.6%. The highest prevalence of LBW was found among mothers whose ages were less than 20 years, who did not receive prenatal care, who were not educated, who were from poor socio-economic conditions. LBW was also severe among infants with the highest birth order and multiple births. This study also identified the mother’s age at the time of childbirth, the status of receiving prenatal care, type of birth (single or multiple), birth order, educational status of the mother, wealth index, and place of residence are the most important determinants that are significantly associated with LBW status of newborns. Conclusions: This study suggests that the Government should take necessary initiatives to address the risk factors which are responsible for the high prevalence of LBW in Bangladesh. This study will also deliver the degree of success in public health policy in Bangladesh and aims to help outline future tactics to lessen the prevalence of LBW. Keywords: Low birth weights (LBW), Multiple Indicator Cluster Survey (MICS), Bangladesh.